Perbedaan Gaya Pengambilan Keputusan Konsumen antara Konsumen Mahasiswa yang Berbelanja Apparel Product secara In-store dan Online - Karlina Mustika Destianti; Bertina Sjahbadhyni (Fakultas Psikologi Universitas Pancasila, 2012)
The increase of online shopping in Indonesia makes the marketing division needs to know the effective technique which may be different with in-store marketing technique. One of the ways to know marketing technique type is through the consumers' decision-making style. This research goal is to see the difference of the decision making type in those selling places, (in-store and online), especially for apparel products. Decision-making style can be known through Consumer Styles Inventory (Sporal & Kendal, 1986). The participants in the research were 110 college students in Jabodetabek area which consist of 55 participants who chose to buy the product online. According to independent sample-test statistics calculation, it is known that there is a significant difference in the quality awareness (the significant score = 0.002, p<0.05). Those who bought the product online were more aware on the quality of the product than those who bought in-store. Therefore, the marketing division should show the products quality to online consumers more than to the in-store consumers so that the marketing will be more effective.